2016
DOI: 10.1016/j.ijppaw.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Oxyspirura petrowi infection leads to pathological consequences in Northern bobwhite ( Colinus virginianus )

Abstract: Debilitating ocular diseases are often reported in avian species. By and large, helminth parasites have been overlooked in avian diseases and regarded as inconsequential. The decline of Northern bobwhite quail (Colinus virginianus) in the Rolling Plains ecoregion of Texas has prompted an investigation of the factors influencing their disappearance. Infection by the eyeworm (Oxyspirura petrowi) has been documented in many avian species; however, the effect it has on its host is not well understood. Heavy eyewor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 11 publications
(28 reference statements)
2
14
0
1
Order By: Relevance
“…Euthanasia and necropsies were performed as described in Dunham et al (2014). Eyeworms were extracted from the eyes by removing the eyeball and associated tissues into a petri dish as outlined in Dunham et al (2016a). Caecal worm collection followed protocols described in Dunham et al (2017b) where caeca were removed and placed in a 20-mesh sieve, then cut into smaller sections to assess caecal worm count.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Euthanasia and necropsies were performed as described in Dunham et al (2014). Eyeworms were extracted from the eyes by removing the eyeball and associated tissues into a petri dish as outlined in Dunham et al (2016a). Caecal worm collection followed protocols described in Dunham et al (2017b) where caeca were removed and placed in a 20-mesh sieve, then cut into smaller sections to assess caecal worm count.…”
Section: Methodsmentioning
confidence: 99%
“…The heteroxenous eyeworm is typically found under the nictitating membrane, lacrimal ducts and glands, and the orbital cavity of the bobwhite (Saunders, 1935; Addison and Anderson, 1969; Robel et al, 2003; Dunham et al, 2014; Bruno et al, 2015; Dunham and Kendall, 2017). Pathological investigations by Dunham et al (2016a) and Bruno et al (2015) found inflammation in the lacrimal duct and lesions on the Harderian gland. This is of great concern when considering these two tissues’ importance to saturation of the eye (Holly and Lemp, 1977) and immune response (Payne, 1994), respectively.…”
Section: Introductionmentioning
confidence: 98%
“…Anecdotal accounts of eyeworm infected bobwhite from the Rolling Plains exhibiting erratic behavior ( Jackson, 1969 ) spurred concerns that these parasites may be causing visual impairment by damaging structures within the eyes of infected individuals. Later, researchers conducted pathological assessments of the eyes of infected bobwhite and confirmed inflammation and damage to the eye tissues and cornea of bobwhite hosts, as well as hemorrhaging of nasolacrimal ducts ( Bruno et al, 2015 ; Dunham et al, 2015 , 2016b ; Hunter, 2016 ). Because bobwhite are highly dependent on their sense of vision when foraging, navigating their environment, and evading predators, the potential effects of impaired vision may be substantial.…”
Section: Using the Woe Framework To Investigate The Role Of Parasitesmentioning
confidence: 99%
“…en Cryptosporidium spp. en myiasis (Abrams et al, 2002;Dubey, 2002;Elias et al, 2008;Lopez et al, 2010;Church et al, 2013;Dunham et al, 2016). Veel van deze parasieten komen echter zelden voor in West-Europa en infecties worden vaak uitsluitend waargenomen bij in het wild levende dieren of in het wild gevangen dieren.…”
Section: Inleidingunclassified